Synthesis and characterization of zinc oxide and tin oxide based nanostructures for gas sensing applications / Tharsika Thabothanayakam - Tharsika, Thabothanayakam (2015)
This thesis focuses on the fabrication of one-dimensional ZnO and SnO2 based nanostructures with various morphologies by a single-step carbon-assisted thermal evaporation process and investigates their gas sensing properties. A mixture of zinc oxide, tin oxide and carbon powders was used as a source material which was loaded in a quartz boat and placed at the center of a tube furnace. A gold coated alumina substrate was placed next to quartz boat at downstream of gas flow direction. The furnace was heated to a particular growth temperature for a certain time while maintaining a constant flow of purified Ar gas. Grey and white fluffy deposits formed on Au coated alumina substrate and at the side and top of the quartz boat, respectively. The deposits collected from alumina substrate and the quartz boat were examined and found to be nanostructured in nature. The effects of different parameters such as growth temperature (800 - 950 °C), growth time (15 min - 120 min) and distance between the source and alumina substrate (3 cm - 12 cm) on the structure of the deposits were studied. Crystallographic phase, microstructure and elemental composition of nanostructures were investigated by X-ray diffractometer (XRD), field-emission scanning electron microscopy (FESEM) and transmission electron microscopy (TEM) equipped with an energy dispersive X-ray spectroscopy (EDS). The crystalline quality of samples was analysed by photoluminescence spectroscopy (PL). The nanostructures were used to fabricate resistor-type sensors on a gold interdigitated alumina substrate. The gas sensing properties of these nanostructures based sensors were studied by measuring their sensitivity towards methane, hydrogen, ethanol and carbon monoxide over different gas concentrations and operating temperatures. Results show that single-crystalline Zn2SnO4 nanowires grew at 834 °C on the Au coated alumina substrate. Nanowires have an average diameter of about 15 to 80 nm and length ranging from two to several tens of micrometers. The white fluffy mass found on a quartz boat exhibited SnO2-core/ZnO-shell nanowires as well as hierarchical nanostructures. Nanostructures deposited on the quartz boat consisted of pristine SnO2 nanowires with a rectangular cross-section, SnO2-core/ZnO-shell nanowires and SnO2-core/ZnO-shell hierarchical nanostructures at a growth time of 15 min, 30 min, and exceeding 60 min, respectively. The hexagonal shape of ZnO branches grew on the ZnO shell layer in the hierarchical nanostructures. Growth mechanisms of Zn2SnO4 nanowires and SnO2-core/ZnO-shell nanostructures are suggested. Zn2SnO4 nanowires based sensors showed excellent sensitivity and selectivity towards ethanol with quick response and recovery times. SnO2-core/ZnO-shell hierarchical nanostructures deposited at 90 min exhibited 5 folds enhanced sensitivity than that of pristine SnO2 nanowires towards 20 ppm ethanol at 400 °C. This improvement in ethanol sensitivity was attributed to highly active sensing sites and the synergistic effect of the encapsulation of SnO2 by ZnO nanostructures. SnO2-core/ZnO-shell hierarchical nanostructures grown for 90 min showed higher sensitivity of 76 compared with Zn2SnO4 nanowires based sensor of 60.8 for 100 ppm ethanol. Specifically, SnO2-core/ZnO-shell hierarchical nanostructures prepared by the single carbon assisted thermal evaporation method are promising candidates for the detection of ethanol with high sensitivity and selectivity against other gases.